Unleashing Prosperity : Productivity Growth in Eastern Europe and the Former Soviet Union - Alam, Asad; Anós Casero, Paloma; Khan, Faruk; Udomsaph, Charles (Washington, DC : World Bank, 2012)
The analysis presented in this report assembles, for the first time, evidence from a variety of sources in the countries of Eastern Europe and the former Soviet Union to show that policy and institutional reforms are important in achieving higher productivity growth. However, significant challenges remain in sustaining that growth. Many countries that started the reform process early, such as the new member states of the European Union, have come to resemble advanced market economies and face challenges in competing successfully in the global economy that are similar to the challenges faced by other European countries. For these new European Union members, the report argues, policies that facilitate innovation and firm expansion will be a key. But for other countries that started the reform process later, such as the countries of Southeastern Europe and the former Soviet Union, there is still a need to address the legacy of transition. For these countries, policies that accelerate restructuring and ease the entry and exit of firms will continue to be essential. This report - part of a series of regional studies of the World Bank's Europe and Central Asia region that has already covered poverty and inequality, the enhancement of job opportunities, trade and integration, migration and remittances, and the challenges posed by aging populations is intended as a contribution to the author thinking about how the World Bank may work more effectively with client states and other partners in the region to promote growth and foster higher living standards in a rapidly changing World.